(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: The aging population has been increasing in recent years, and functional impairments in older adults, linked to various comorbidities, may raise mortality risks in this population. Additionally, another concern is the rise in obesity levels among older adults. However, it is still unclear to what extent body mass index can impact the functionality of older adults. Objective: To verify the correlation between Body Mass Index (BMI) and functionality in older adults. Methods: This is a cross-sectional observational correlational study. The sample consisted of 99 older adults of both sexes. BMI, functional mobility (Timed Up and Go test), isometric strength (handgrip dynamometer), functional muscle fitness (Sit and Stand test), and flexibility (Sit and Reach test) were assessed. Correlation analyses were performed using the Spearman test. Significance was set at p < 0.05. Results: Body mass index was negatively correlated with flexibility (p < 0.001) and functional muscle fitness (p < 0.001), regardless of sex, age, and education. Muscle strength, functional mobility, and the number of falls showed no significant correlation. Conclusion: Older adults with higher obesity levels exhibited lower functional muscle fitness and flexibility.